2019
DOI: 10.1186/s12929-019-0499-8
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinus officinalis L. (rosemary) as therapeutic and prophylactic agent

Abstract: Rosmarinus officinalis L. (rosemary) is a medicinal plant native to the Mediterranean region and cultivated around the world. Besides the therapeutic purpose, it is commonly used as a condiment and food preservative. R. officinalis L. is constituted by bioactive molecules, the phytocompounds, responsible for implement several pharmacological activities, such as anti-inflammatory, antioxidant, antimicrobial, antiproliferative, antitumor and protective, inhibitory and attenuating activities. Thus, in vivo and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
172
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(193 citation statements)
references
References 216 publications
(209 reference statements)
2
172
0
19
Order By: Relevance
“…Nowadays, the development of pharmaceutical industry allows the direct use of natural bioactive substances, such as rosmarinic acid, extracted from plants with a high therapeutic power. RA, a common component of many herbs is said to possess many important biological activities, mainly anti-inflammatory, anti-oxidative, anti-apoptotic, and anti-fibrotic (Oliveira et al 2019;Bahri et al 2017). Exact mechanism of RA action is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the development of pharmaceutical industry allows the direct use of natural bioactive substances, such as rosmarinic acid, extracted from plants with a high therapeutic power. RA, a common component of many herbs is said to possess many important biological activities, mainly anti-inflammatory, anti-oxidative, anti-apoptotic, and anti-fibrotic (Oliveira et al 2019;Bahri et al 2017). Exact mechanism of RA action is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…1) is a dietary, polyphenolic compound widely distributed, e.g., in rosemary, Perilla frutescens, oregano, and mint. Its beneficial, biological effects, including anti-inflammatory, anti-oxidative, anti-bacterial, and anti-cancer, have been reported (Oliveira et al 2019). It is said that RA can promote several pharmacological effects due to specific interactions with different parts of organic systems (Scheckel et al 2008;Karthik et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The main component of the dark-forced young leaves was bornyl acetate (26.1%), which was present in slightly but not significantly lower ratio in the essential oils of lightgrown younger leaves, and in significantly lower amounts in light-grown or dark-forced older leaves (2.5% and 2.1%, respectively). The pharmacologically important compounds such as α-pinene, 1.8-cineole and camphore, which are responsible for the antirheumatic effect of rosemary leaf (Borges et al, 2018;De Oliveira et al, 2019), were present in a low ratio in the dark-forced leaves, especially in the youngest leaves. Therefore, from a therapeutic aspect, the lack of light adversely affects the essential oil composition of rosemary leaves.…”
Section: The Effect Of Prolonged Darkness On the Essential Oil Composmentioning
confidence: 99%
“…Our aim was to check whether such tubuloreticular structures were characteristic for the plastids of the peltate glandular hairs of other medicinally and economically important Lamiaceae species such as for example rosemary (Rosmarinus officinalis) (Borges et al, 2018;De Oliveira et al, 2019) and whether their presence or structure was influenced by darkness. This question is evenmore important because data about the structural and developmental plasticity of secretory plastids are rather scarce (Solymosi and Keresztes, 2012) and the role of light in the biosynthesis of the essential oil components also needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are many studies on the usefulness of bioactive substances of rosemary plants on human health as it was used to treat arthritis, diabetes, memory loss and hair restoration (El Omri et al, 2010). Rosemary has a great potential due to secondary biomolecules which have been characterized as antidiabetic (Yen et al, 2015), antimicrobial (Almela et al, 2006), spasmolytic, carminative, hepatoprotective, antiviral and anticarcinogenic agents (Bozin et al, 2007), and reported also to have antihyperglycemic, anti-in ammatory and antiproliferative activities (Oliveira et al, 2019). Some rosemary extracts have been shown strong inhibitory effect against human respiratory syncytial virus infection (Shin et al, 2013).…”
Section: Rosmarinus O Cinalismentioning
confidence: 99%